2022
DOI: 10.20377/jfr-695
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and changes in the level of contact between older parents and their non-coresident children: A European study

Abstract: Objective: The present study aims to investigate changes in the frequency of parent-child contact among Europeans aged 65 years and over within the context of the COVID-19 pandemic, while recognizing heterogeneity within the group of older adults. Background: Physical distancing measures have been implemented worldwide to curb the spread of the COVID-19 pandemic. Although this policy has proven to be effective in flattening the curve, it undoubtedly posed a serious challenge to intergenerational relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…This paper, based on wave 6, showed the generation of active ageing profiles, and we assume that the changes in the two following waves would be smaller due to the short difference in dates. However, the COVID-19 pandemic outbreak could have altered older adults behaviors and quality of life due to i) the consequences of the impact of the disease, and ii) the measures imposed for preventing the spread of the coronavirus, showed by other research [139][140][141][142][143][144][145]. In this sense, the SHARE-ERIC designed and developed the SHARE-COVID19 survey (1 and 2 waves) (http://www.share-project.org/ share-covid19.html) with the objective of identifying the lockdown effects over older-adult population.…”
Section: Limitations and Future Linesmentioning
confidence: 99%
“…This paper, based on wave 6, showed the generation of active ageing profiles, and we assume that the changes in the two following waves would be smaller due to the short difference in dates. However, the COVID-19 pandemic outbreak could have altered older adults behaviors and quality of life due to i) the consequences of the impact of the disease, and ii) the measures imposed for preventing the spread of the coronavirus, showed by other research [139][140][141][142][143][144][145]. In this sense, the SHARE-ERIC designed and developed the SHARE-COVID19 survey (1 and 2 waves) (http://www.share-project.org/ share-covid19.html) with the objective of identifying the lockdown effects over older-adult population.…”
Section: Limitations and Future Linesmentioning
confidence: 99%
“…Furthermore, our research sheds light on intergenerational contact dynamics during the pandemic. While previous research on intergenerational contact mostly focused on the first wave of the pandemic [ 15 , 20 , 30 , 31 ], when there were strong restrictions to face-to-face interactions with other people, it is important to also analyze intergenerational contact in other phases of the pandemic. Indeed, intergroup contact habits might change over time, and reduction in intergenerational contact in a specific time point might have long lasting effects.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Podhorecka et al [ 32 ] found that only a minority of Polish respondents diminished or avoided contact with older people (data collected in February 2021). However, Vergauwen et al [ 31 ] and Podhorecka et al [ 32 ] did not distinguish between direct vs. telephone and online contact in their analysis. Instead, Arpino, Pasqualini, and Bordone [ 20 ] distinguished between physical (direct, face-to-face) and non-physical (e.g., video-calls, instant messaging) contact, and analyzed older people’s intergenerational contact during the first lockdown in Italy, Spain, and France (April 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with a higher number of (in-person) social contacts seem to have more occasions to provide instrumental help to others. Vergauwen et al ( 2022 ) found that, despite stringent contact policies during the COVID-19 pandemic, older adults were generally not likely to experience a decrease in contacts and assumed that increased support (including digital contacts) for parents might explain this effect. Further, reciprocity is seen to play an important role in the exchange of social support.…”
Section: Methodsmentioning
confidence: 99%